Penerapan Design Thinking dalam Perancangan Pion Karakter Board Game Laskar Kristus untuk Usia 8-12 Tahun - Hanung Sekar Larasati Enggaringtyas; Mahimma Romadhona; Widyasari Widyasari (Lembaga Pengembangan Kinerja Dosen, 2026)
The Fruit of the Spirit is an important theological value to teach children because it contains points for everyday behavior. However, learning about the Fruit of the Spirit often encounters obstacles and is difficult for children aged 8-12 years to understand because it is considered too abstract and difficult to convey in simple language. Furthermore, obstacles come from the learning media used which are still conventional. Therefore, effective learning media are needed that can attract the interest and motivation of children to want to learn and apply the Fruit of the Spirit in everyday life, such as board games. In board games, there are components that can attract emotions and can be used as media, namely character pawns. The method used is the Design Thinking method with descriptive analysis. This approach is used to analyze data from the results of observations, interviews, literature studies, and questionnaires, as well as to develop concepts and design results. Thus, the character pawns can be created with a human-centered design approach, which is able to create visuals that have a close relationship with children's psychology.